Якість життя у жінок з поєднаними гіперпроліферативними процесами жіночої репродуктивної системи - Потапов, В.О.; Івах, В.І.; Донська, Ю.В.; Сімонова, Н.В.; Медведєв, М.В. (Таврический медико-биологический вестник, 2013)
В работе изучена выраженность симптомов и качество жизни у женщин с лейомиомой матки, а также при сочетанных гиперпролиферативных процессах женских половых органов (лейомиома матки, гиперплазия эндометрия и эндометриоз). Было показано, что наибольшая выраженность симптомов и снижение качества жизни наблюдались при сочетанных гиперпролиферативных процессах женских половых органов. Для женщин с лейомиомой матки и эндометриозом был наиболее выражен болевой синдром, тогда как для сочетания лейомиомы матки и гиперплазии эндометрия был более характерен геморрагический синдром. Полученные данные позволят в ходе дальнейших исследований оценить эффективность различных методов лечения сочетанных гиперпролиферативных процессов женской репродуктивной системы. The study is devoted to estimation of symptoms and quality of life in women with uterine leiomyomas, as well as co-hyperproliferative processes of the female genital organs (the uterine leiomyoma, endometrial hyperplasia, and endometriosis). It has been shown that the highest expression of symptoms and the lowest quality of life are observed in women with combined hyperproliferative processes of the genital organs. For women with uterine leiomyoma and endometriosis, the most pronounced symptom was pain, whereas the combination of uterine leiomyoma and endometrial hyperplasia were characterized predominantly by hemorrhagic syndrome. The data obtained in the course of further studies will help to evaluate the effectiveness of different treatments of combined hyperproliferative processes of the female reproductive system.